Effect of aging on resilient modulus of hot mix asphalt mixtures - Idham, M. K. (2013)
Asphalt hardens as a result of an aging process. This study was undertaken to determine the effect of field aging simulated by laboratory aging method of different hot mix asphalt (HMA) mixture. Three types HMA mixtures were used for this study namely Asphaltic Concrete with 10 mm nominal maximum aggregate size (AC 10), Aspaltic Concrete 28 mm (AC 28) and Porous Asphalt 10 mm (PA 10). The resilient modulus test was carried out as an indicator of the performance at a 25 °C and 40 °C. Generally, all samples show similar trend which aged mixture produced slightly higher resilient modulus compared to unaged mixture while an increase in temperature from 25 °C to 40 °C might reduced the resilient modulus up to 88%. This study also found that the difference increment of resilient modulus after the aging process attributed by asphalt content, air void and gradation of respective mixtures.